Introducing Tesla turbine to enhance energy efficiency of refrigeration cycle - Yahya Sheikhnejad; Jo\~ao Sim\~oes; Nelson Martins (Energy Reports, 2020)
In this study, a new application of a Tesla turbine (TT) is presented in which a TT is introduced as a promising solution to enhance the energy efficiency of refrigeration cycles. For this special purpose, a TT is represented as a regenerative system that minimizes the wasted energy without compromising the system output quality or sacrificing standards of design and move one step forward, towards more sustainable industries. To achieve this goal, a 3D thermohydrodynamic analysis of the Newtonian turbulent compressible flow of high-pressure methane through a Tesla turbine has been performed under different configurations and operational conditions. Methane was defined as a real gas through the Redlich-Kwong equation of state. The complex unstructured grid generation was employed to produce a low-skewness mesh for a CFD model on the commercial software of ANSYS Fluent for simulation of heat and mass transfer by FVM. As a result of the present study, practical design rules are proposed to support engineers defining optimized TTs for predetermined operating conditions, namely regarding power output, disc sizes and angular velocity.
Keywords: 330; Energy efficiency; Compressible turbulent flow; High-pressure methane; Refrigeration cycles; Tesla turbine (TT)